Analisis Gaya Pada Alat Bending Roll Menggunakan Metode Elemen Hingga Dan Eksperimental - Dian Haryanto; Efi Afrizal; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bending Roll is a tool used to make curves, which are widely used in the field of construction work. The Bending Rolltool made by Tongam and Aweng (2018) has not been tested. To analyze the performance of the Bending Roll tool using thefinite element method then compared with direct testing. Testing through finite element method Finite element methodsoftware is used, namely Abaqus. That testing directly specimens used there are two types, plate and Hollow. For platespecimens, the rolling process is tested by adding a load using a hydraulic jack and the compressive force measured by thepressure gauge. Whilst Hollow specimens a strain gauge is also used to measure the strain that occurs during rolling. Thegoal is to be able to see the phenomena that occur in the specimen during rolling. The results of the most ideal specimen tobe carried out on a tool is a specimen with a thickness of 3 mm. On the 3 mm plate the stresses are large and can formyoung specimens with a small force. When the force used is small, it will extend the life of the bending roll tool. If calculatedthe level of difference in measurements that occur is not so big between experimental measurements and simulationmeasurements.Key words: Bending Roll, finite element, pressure gauge, strain gauge.